Hubungan Lama Rawat Inap Dengan Kemampuan Pasien Dalam Mengontrol Halusinasi Di RSUD Madani Provinsi Sulawesi Tengah : Penelitian - Siti Mutia; Djuwartin; Sisilia Rammang (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Background: Schizophrenia is a chronic psychiatric disorder that causes perceptual disorders such as hallucinations. The patient’s inability to control hallucinations can pose a risk to themselves, others, and the surrounding environment. The length of the hospitalization is suspected to affect the patient's ability to recognize and control hallucinations through intensive therapy and assistance in the hospital. Based on data from RSUD Madani, Central Sulawesi Province, which shows a high number of cases of hallucinations. of this study is to analyze the relationship between the length of hospitalization and patients' ability to control hallucinations at RSUD Madani, Central Sulawesi Province. Method: This study used a type of quantitative research with a cross-sectional approach. The study population was 78 hallucination patients who were hospitalized at RSUD Madani. The sampling technique used was proportionate stratified random sampling with a sample of 37 respondents. The research instrument was in the form of an observation sheet on the ability to control hallucinations. The data was analyzed using the Chi-Square test Result: Based on the results of univariate analysis for a long time, most of the old categories were 23 respondents (62.2%), while the ability to control hallucinations was mostly good in the category of 21 respondents (56.8%). Based on the results of statistical tests using the Chi-Square test, the result was obtained with a p-value of p-value = 0.000(<0.05), indicating a relationship between the length of treatment and the patient's ability to control hallucinations The. Conclusion: There is a Long Relationship of Hospitalization with Patients' Ability to Control Hallucinations at RSUD Madani , Central Sulawesi Province. Suggestion: It is hoped that the hospital will continue to improve the quality of psychiatric nursing services and provide a comprehensive therapy program during the treatment period to improve the patient's ability to control hallucinations